Vulnerability, threats, and attacks in E Payments System: Security Solutions - Kiran, Dr. Chitra (International Journal of Psychosocial Rehabilitation, 2020)
the current payment system through online applications has to trend at a furious pace. The various and multiple numbers of online transaction methods (i.e., E-payment systems) has been proposed for various security aspects. However, with the increasing of E-payment methods, the various cyber-attacks methods are also increasing at an advanced level. Therefore, in this study have presented a terminology of E-payment system including with various existing methods. Also illustrates security provisions and solutions. The primary objective is to provide the roadmap of E-payment mechanism and its opportunities for future scope.